Distal Vacuolar Myopathy in Cystinosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Distal vacuolar myopathy in 13 post-renal-transplant cystinosis patients, ages 17 to 27 years, and studied at multiple centers, is reported from the National Institute of Child Health and Human Development, Bethesda, MD.